POST-MORTEM EXAMINATION AFTER SUNSET (NIGHT AUTOPSY): A SCOPING REVIEW (Journal of Forensic Medicine & Toxicology, 2024)
Cognizance by the Govt. of India regarding the issue of post-mortem examination after sunset (night autopsy) is welcoming step towards Humanitarian Forensic and had been a key demand pending since long. This article attempts to understand the medicolegal and administrative challenges in its implication with possible solutions. This review article will provide valuable insights from the perspective of forensic experts while developing comprehensive guidelines regarding conducting night autopsies.
Keywords: Autopsy; Night autopsy; Post-mortem examination; Sunset